2023
DOI: 10.1039/d3tc02570e
|View full text |Cite
|
Sign up to set email alerts
|

Indoor organic solar cells for low-power IoT devices: recent progress, challenges, and applications

Rakesh Suthar,
Hemraj Dahiya,
Supravat Karak
et al.

Abstract: In the last few years, organic solar cells have emerged with potential applications in abundant low-power indoor Internet of Things devices, such as smart watches, calculators, remote controls, and other devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 129 publications
0
2
0
Order By: Relevance
“…3 rd generation) are considered as highly relevant PV technologies compared to more conventional inorganic devices (silicon-based systems or thin film technologies), due to their rising performance under full sun and potentially low manufacturing costs and energy payback times [20], [21]. Recent studies have shown the importance of organic photovoltaics (OPVs) for energy harvesting in indoor IoT context [22], [23], [24], [25], [26].…”
Section: Introductionmentioning
confidence: 99%
“…3 rd generation) are considered as highly relevant PV technologies compared to more conventional inorganic devices (silicon-based systems or thin film technologies), due to their rising performance under full sun and potentially low manufacturing costs and energy payback times [20], [21]. Recent studies have shown the importance of organic photovoltaics (OPVs) for energy harvesting in indoor IoT context [22], [23], [24], [25], [26].…”
Section: Introductionmentioning
confidence: 99%
“…Blending with Y6, D18 demonstrated >18% PCE, marking a notable advance in the field of organic photovoltaics. Since its initial demonstration, D18 and its derivatives have exhibited exceptional performance across a variety of applications, including highly efficient single-junction devices [22,23] , stretchable electronics [24] , thick-film devices [25] , efficient all-polymer systems [26,27] , indoor photovoltaics [28,29] , devices with enhanced stability [30−32] , green solvent-processed devices [33,34] , and tandem devices [35−37] . This article will present the strategies employed with D18 and its derivatives in single-junction OSCs for achieving PCEs above 19% (Fig.…”
mentioning
confidence: 99%